Creating a bully-free Sierra Leone: a comprehensive approach involving prevention, intervention, and support for victims and bullies by teachers, parents, and community leaders - Osborne, Augustus (Frontiers in Education, 2024)
Bullying poses a substantial challenge to the educational and social development of children in Sierra Leone. This conceptual analysis explores the critical roles of teachers, parents, community leaders, and other stakeholders in preventing and addressing this issue. It emphasizes the importance of a multi-faceted approach by examining the complexities of bullying within the Sierra Leonean context. The conceptual analysis differentiates between prevention, intervention, and postvention strategies, outlining specific actions aimed at both bullies and victims. Effective bullying prevention strategies include teacher training, parent involvement, and community collaboration, while intervention efforts focus on immediate support for victims and appropriate consequences for bullies. Additionally, postvention actions are discussed to support recovery and healing for those affected. It highlights the need for sustained efforts, data-driven approaches, and policy development to create a safer and more inclusive learning environment for all students in Sierra Leone.